2011
DOI: 10.1111/j.1462-5822.2011.01716.x
|View full text |Cite
|
Sign up to set email alerts
|

The Type VI secretion system of Burkholderia cenocepacia affects multiple Rho family GTPases disrupting the actin cytoskeleton and the assembly of NADPH oxidase complex in macrophages

Abstract: SummaryBurkholderia cenocepacia is a Gram-negative opportunistic pathogen of patients with cystic fibrosis and chronic granulomatous disease. The bacterium survives intracellularly in macrophages within a membrane-bound vacuole (BcCV) that precludes the fusion with lysosomes. The underlying cellular mechanisms and bacterial molecules mediating these phenotypes are unknown. Here, we show that intracellular B. cenocepacia expressing a type VI secretion system (T6SS) affects the activation of the Rac1 and Cdc42 R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(94 citation statements)
references
References 77 publications
2
90
1
1
Order By: Relevance
“…Previous work in our laboratory demonstrated that the B. cenocepacia T6SS is essential for virulence in vivo (Hunt et al, 2004), and also required for the formation of actin-rich protrusions in infected macrophages (Aubert et al, 2010(Aubert et al, , 2008Rosales-Reyes et al, 2012) through inactivation of Rac1 (Flannagan et al, 2012;Rosales-Reyes et al, 2012). To determine whether the suhB Bc deletion affects T6SS function, we infected macrophages with B. cenocepacia-K56-2, DsuhB Bc and DsuhB Bc -pSM67.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work in our laboratory demonstrated that the B. cenocepacia T6SS is essential for virulence in vivo (Hunt et al, 2004), and also required for the formation of actin-rich protrusions in infected macrophages (Aubert et al, 2010(Aubert et al, , 2008Rosales-Reyes et al, 2012) through inactivation of Rac1 (Flannagan et al, 2012;Rosales-Reyes et al, 2012). To determine whether the suhB Bc deletion affects T6SS function, we infected macrophages with B. cenocepacia-K56-2, DsuhB Bc and DsuhB Bc -pSM67.…”
Section: Methodsmentioning
confidence: 99%
“…The ability of B. cenocepacia to infect and persist in macrophages is associated with delayed phagolysosomal fusion (Huynh et al, 2010;Keith et al, 2009;Lamothe et al, 2007;Rosales-Reyes et al, 2012). To identify whether suhB Bc plays a role in the ability of B. cenocepacia to survive intracellularly we deleted the suhB Bc gene in the MH1K strain, an isogenic derivative of strain K56-2 that exhibits high susceptibility to gentamicin (Hamad et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…B. cepacia adopts an extracellular or intracellular lifestyle (23,24). This bacterium can survive within a variety of eukaryotic cells such as amoebae, epithelial cells, and macrophages (25)(26)(27)(28).…”
mentioning
confidence: 99%
“…The type IV secretion system has been implicated in the ability of B. cenocepacia to survive macrophage phagocytosis by evasion of lysosomal fusion [89]. The type VI secretion system has been shown to reduce production of reactive oxygen species inside macrophages [90].…”
Section: Burkholderia Cenocepaciamentioning
confidence: 99%